Development of Web-Based Science Learning Module in Improving the Students’ Understanding of Eco-Literacy - Amalia Firdausi; Fitria Eka Wulandari (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
This study aims to determine the feasibility of the module in improving students' understanding of eco-literacy. This research is development research using the 4D development model with ten students as research participants. The learning module developed is validated by two competent validators from internal and external campuses. The feasibility of the module includes the validity and reliability of the module as measured by the validation questionnaire sheet. The validation results show that the module obtained an average score of 3.66 (very valid category), with the reliability score of 0.83 (real category). The research data were analyzed descriptively and quantitatively. Students' understanding was measured on the competency test in the module on the pretest and posttest after giving the treatment. The results of the module trial calculated using the N-gain formula indicate that the effectiveness was under the high category with a score of 0.703 with an average pretest and posttest values of 43.7 and 83.49, respectively. Based on the study results, it can be concluded that the web-based science learning module developed is valid, reliable, and effective in improving students' understanding of eco-literacy.